PENGARUH BUDAYA DAN SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PADA PT. BINA LANGGENG LESTARI (TONY MOLY COSMETIC) MEDAN - Efrizal Adil (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2016)
The purpose of this paper is to test and find out the cultural and sociali influences towardpurchasing decisions, and also to know wheter cultural and social effect partially positiveand significant and simultants against purchasing decisionson PT.Bina Langgeng Lestari(Tony Moly Cosmetic) Medan. A consumer survey by using quantitative methods andinvolver 98 respondents succesfully carried out using the division of the questionnaire atthe counter of Tony Moly Cosmetic Medan. Based on the results of the study showed thatsimultaneous cultural and social variables have positive and significant influence onpurchasing decisions, then the hypothesis is accepted. Cultural and social partially positiveand significant impact on purchasing decisions at PT. Bina Langgeng Lestari (Tony MolyCosmetic) field, then the hypothesis is accepted.